HUBUNGAN ANTARA PRAKTEK MANAJEMEN PEMELIHARAAN DENGAN KEJADIAN AVIAN INFLUENZA PADA PETERNAKAN AYAM PEDAGING DI SEKTOR 3 MILIK MITRA PT. DUTA TECHNOVET DI DIY SELAMA SATU SIKLUS PEMELIHARAAN - Sadarman Sadarman; A.E.T.H. Wahyuni; C.R. Tabbu; S. Budhiarta (State Islamic University of Sultan Syarif Kasim Riau, 2011)
The control strategies of avian influenza (AI) inpedaging operations primarily depend on tight biosecuritymeanwhile management practices on farm. This experiment was designed to study the relationship between the level ofbiosecurity and the incidence of AI in one rearing period ofpedaging farms at sector-3 with an opened house system. Thisstudy was done in contractpedaging company farms of PT. Duta Technovet which has a minimum of 1.000 chickens. Thisstudy was conducted in 18 houses (n) ofpedaging farms which were distributed in 3 different villages of 3 differentsubdistricts and districts in Yogyakarta Special Region. Sixpedaging houses were selected from Sendang Sari Village ofPajangan subdistrict of the district of Bantul; 6 pedaging houses were from Getas Village of Playen subdistrict of the district of Gunungkidul; and 6pedaging houses were from Pakem village of Pakem subdistrict of the district of Sleman. The judgment based on the score of the prepared questionnaire for thepedaging farmers. Isolation of AI virus employing cloacal swab was done in the Virology Laboratory of Balai Besar Veteriner (BBVet) Wates. Data were collected and analyzed with the Fisher's exact test (FET), using the software SPSS of Windows version 15.0. The results of this study indicate that the presence of stable air ventilation sufficient to give significant results on the incidence of AI disease inpedagings, with P <0.01.